THE EFFECTS OF COLCHISIN IN THE TREATMENT OF CHRONIC LIVER DISEASE - Mehmet ALTIN; Saadeddin HÜLAGÜ; Sabahattin GÜL; Levent DEMİRTÜRK; Gündüz ÖZTÜRK; Mesut BAŞAK; Mehmet DANACI; Ali ÖZCAN; Levent DUMANHAN; Sedat YÜRÜTKEN (Turkish Journal of Gastroenterology, 2020)
-